2020
DOI: 10.3389/fbioe.2020.00943
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Peptide MHC Specific TCR Expressing T-Cell Membrane Camouflaged PLGA Nanoparticles for Treatment of Melanoma Skin Cancer

Abstract: Melanoma is one of the most aggressive skin cancers, and the American Cancer Society reports that every hour, one person dies from melanoma. While there are a number of treatments currently available for melanoma (e.g., surgery, chemotherapy, immunotherapy, and radiation therapy), they face several problems including inadequate response rates, high toxicity, severe side effects due to non-specific targeting of anti-cancer drugs, and the development of multidrug resistance during prolonged treatment. To improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Recently, PLGA-NPs loaded with trametinib and coated with membrane from T cell hybridoma have also been used for the treatment of melanoma [ 63 ]. These NPs were found to be very stable and drug release was dependent on the amount of membrane used due to the presence of a melanoma-specific anti-gp100/HLA-A2 T-cell receptor (TCR) that promotes binding kinetics and cell uptake.…”
Section: Principal Types Of Cell Membranes Employedmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PLGA-NPs loaded with trametinib and coated with membrane from T cell hybridoma have also been used for the treatment of melanoma [ 63 ]. These NPs were found to be very stable and drug release was dependent on the amount of membrane used due to the presence of a melanoma-specific anti-gp100/HLA-A2 T-cell receptor (TCR) that promotes binding kinetics and cell uptake.…”
Section: Principal Types Of Cell Membranes Employedmentioning
confidence: 99%
“…Furthermore, these NPs were endocytised to a greater extent by tumor cells compared to uncoated NPs, which led to significant tumor killing in vitro. Therefore, these nanoparticles could be used in therapy associated with melanoma [ 63 ].…”
Section: Principal Types Of Cell Membranes Employedmentioning
confidence: 99%
“…The liposome-treated T cells managed a 5.2-fold reduction in tumor volume and gave a survival advantage of over 14 days over the mice treated with just T cells. As an alternative approach to NP hitchhiking via T cell surface or compartment, our group showed that T cell membrane-coated NPs actively target tumor regions via their specific T cell receptors called TCR [ 15 ] . In this study, chemotherapeutic drug Trametinib loaded PLGA NPs were coated with the membranes of melanoma-specific “anti-gp100/HLA-A2” T-cell receptor (TCR) bearing T cells.…”
Section: Cell Types Used In Cell- and Cell Membrane-based Drug Delivementioning
confidence: 99%
“…Despite the potential of artificial APCs for adaptive cell-based therapy and the advantage of synthetic particles to penetrate lymph nodes after subcutaneous administration, the construction of artificial systems is complex and time consuming [25][26][27] . Furthermore, epitope-embedded MHC multimer complexes can be engineered only individual epitope of interest has been identified beforehand 28 . Additionally, introducing certain membrane proteins of APCs can solely confer with partial function of the interaction with T cells, largely limiting their application 29 .…”
Section: Introductionmentioning
confidence: 99%